Kontribusi Usaha Ternak Ayam Ras Pedaging terhadap Pendapatan Petani Di Desa Sungai Malang Kecamatan Amuntai Tengah Kabupaten Hulu Sungai Utara - Purna Kusumayana; Rezqi Hatimah (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2011)
Destination from this observation is understand (i) structure costs, revenue, income attempt ranch chicken in Sungai Malang village Isaland Amuntai Tengah, (ii) structure costs, revenue, income attempt rice in Sungai Malang village Kecamatan Amuntai Tengah, (iii) contribution big attempt chicken to income attempt rich in Sungai Malang Village Amuntai Tengah Distric,. (iv) problem ascertain poltry in administer attempt chicken. This research was conducted in Sungai Malang Village Amuntai Tengah District Hulu Sungai Utara Regency from March – June 2011. Used sensus method at 42 farmer respondents. The results referred that total cost from chicken livestock in Sungai Malang Village District of Central Amuntai was Rp 10.375.697,-, with revenue about Rp 16.960.114,-/kg and income equal to Rp 57.105.886,-. Total costs of rice in Sungai Malang village Central Amuntai District was Rp 2.662.504,-, with revenue about Rp 5.317.500,-/blek and income equal is Rp 3.800.667,-. Contribution chicken livestock to income was 91 % from total income occur farmer